A world not made for us : topics in critical environmental philosophy - Peterson, Keith R. (Suny series in environmental philosophy and ethics, 2020)
"In A World Not Made for Us, Keith R. Peterson provides a broad reassessment of the field of environmental philosophy, taking a fresh and critical look at three classical problems of environmentalism: the intrinsic value of nature, the need for an ecological worldview, and a new conception of the place of humankind in nature. Peterson makes the case that a genuinely critical environmental philosophy must adopt an ecological materialist conception of the human, a pluralistic value theory that emphasizes the need for value prioritization, and a stratified categorical ontology that affirms the basic principle of human asymmetrical dependence on more-than-human nature. Integrating environmental ethics with the latest work in political ecology, Peterson argues it is important to understanding that the world is not made for us, and that coming to terms with this fact is a condition for survival in future human and more-than-human communities of liberation and solidarity"--